2015
DOI: 10.1007/s10753-015-0209-y
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Suppressed Inflammatory Reactions in IL-1β-Stimulated Human Periodontal Ligament Cells

Abstract: Vitamin D has important roles on control of calcium and phosphate levels in the body. However, the role of vitamin D on the pathogenesis of periodontal disease is still uncertain. Therefore, we examined the effect of the hormonal form of vitamin D, calcitriol, on inflammatory responses of human periodontal ligament cells (HPDLC). We detected vitamin D receptor expression in non-stimulated HPDLC. Calcitriol inhibited interleukin (IL)-6, IL-8, CC chemokine ligand (CCL) 20, CXC chemokine ligand (CXCL) 10, and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…Our data demonstrated that continuous local LPS injection into the gingival sulcus, which is a common method for generating experimental periodontitis in rats for research purposes, could induce local inflammatory responses, bone damage, and finally periodontitis . During the development of periodontitis, systemic calcitriol administration via oral gavage was used to influence bone resorption because substantial evidence indicates that calcitriol can act as a therapeutic agent for periodontal disease . Based on micro‐CT analysis, we found that rats that underwent LPS injection while simultaneously receiving calcitriol intervention (LPS + Cal group) exhibited decreased bone resorption compared with those without calcitriol intervention (LPS group).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Our data demonstrated that continuous local LPS injection into the gingival sulcus, which is a common method for generating experimental periodontitis in rats for research purposes, could induce local inflammatory responses, bone damage, and finally periodontitis . During the development of periodontitis, systemic calcitriol administration via oral gavage was used to influence bone resorption because substantial evidence indicates that calcitriol can act as a therapeutic agent for periodontal disease . Based on micro‐CT analysis, we found that rats that underwent LPS injection while simultaneously receiving calcitriol intervention (LPS + Cal group) exhibited decreased bone resorption compared with those without calcitriol intervention (LPS group).…”
Section: Discussionmentioning
confidence: 90%
“…33 During the development of periodontitis, systemic calcitriol administration via oral gavage was used to influence bone resorption because substantial evidence indicates that calcitriol can act as a therapeutic agent for periodontal disease. 13,[21][22][23] Based on micro-CT analysis, we found that rats that underwent LPS injection while simultaneously receiving calcitriol intervention (LPS + Cal group) exhibited decreased bone resorption compared with those without calcitriol intervention (LPS group). When bone destruction was analyzed by micro-CT-reconstructed 3D models, the LPS + Cal group showed in a higher BV/TV ratio than the LPS group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we found increased expression of TNF-a, a gene stimulated by IL-33 [29], and IL-1B, a gene involved in the activation of IL-33 [30]. Finally, we found that RV induced genes that are targets of 25(OH)-VitD3, such as Gene arrays of RNA from in-vitro rhinovirus (RV)-infected peripheral blood mononuclear cells (PBMCs) of preschool children with asthma revealed the induction of innate lymphoid cell type 2 (ILC2)-associated genes.…”
Section: Gene Arrays From In-vitro Rv-infected Pbmcs From Preschool Cmentioning
confidence: 74%